(untitled) (Revista Brasileira de Contabilidade e Gestão, 2013)
By using mathematical modeling to determine analytical curves, equations and coefficients for chemical parameters, it aims to facilitate laboratory work. Nitrogen and phosphorus parameters are found in the most diverse ways in the environment. The method used to determine these parameters is colorimetric, based on the Beer-Lambert Law. The use of standard samples serves as a comparison procedure, where samples that present concentrations in a previously established range are analyzed. Analytical curves are obtained using the linear curve fitting method, whose equation will serve as a reference for future determinations of concentrations. For each curve, a linear correlation coefficient is generated, which indicates how good the fit is. The analytical curves obtained are extremely important, acting as a tool in determining the concentrations of the parameters.